TRANSALP - DEEP CRUSTAL VIBROSEIS AND EXPLOSIVE SEISMIC PROFILING IN THE EASTERN ALPS - Lüschen E.; Gebrande H.; Borrini D.; Lammerer B.; Millahn K.; Neubauer F.; Nicolich R. (My University, 2006)
The TRANSALP consortium, comprising institutions from Italy, Austria and Germany, carried out deep seismic reflection measurements in the Eastern Alps between Munich and Venice in 1998, 1999 and 2001. In order to complement each other in resolution and depth range, the Vibroseis technique was combined with simultaneous explosive source measurements. Additionally, passive cross-line recording provided three-dimensional control and alternative north-south sections. Profits were obtained by the combination of the three methods in sectors or depths where one method alone was less successful. The TRANSALP sections clearly image a thin-skinned wedge of tectonic nappes at the northern Alpine front zone, unexpected graben or half-graben structures within the European basement, and, thick-skinned back-thrusting in the southern frontal zone beneath the Dolomite Mountains. A bi-vergent structure at crustal scale is directed from the Alpine axis to the external parts. The Tauern Window obviously forms the hanging wall ramp anticline above a southward dipping, deep reaching reflection pattern interpreted as a tectonic ramp along which the Penninic units of the Tauern Window have been up-thrusted. The upper crystalline crust appears generally transparent. The lower crust in the European domain is characterized by a 6-7 km thick laminated structure. On the Adriatic side the lower crust displays a much thicker or twofold reflective pattern. The crustal root at about 55 km depth is shifted around 50 km to the south with respect to the main Alpine crest. © 2005 Elsevier B.V. All rights reserved.
Keywords: BI-VERGENT OROGENY; EASTERN ALPS; SEISMIC PROFILING; SUB-TAUERN-RAMP; TRANSALP; VIBROSEIS